Leslie Preston Day, HeidiM.C. Dierckx, Kimberly Flint-Hamilton, Geraldine C. Gesell, Kevin T. Glowacki, Nancy L. Klein, David S. Reese and Lynn M. Snyder. Kavousi IIC: The Late Minoan IIIC Settlement at Vronda. Specialist Reports and Analyses. Kavousi - Schoep, Ilse (Journal of Greek Archaeology, 2017)
This is the third volume in the series publishing the cleaning and excavation of the site of Vronda in the Kavousi area. The first volume, Kavousi IIA, was devoted to the excavation, stratigraphy, and architecture of the houses and their finds on the summit of the Vronda ridge (Buildings A-B, C-D, J-K, and Q), along with earlier (Building P) and later (Building R) structures around them. The second volume, Kavousi IIB , focuses on the buildings on the slopes of the Vronda ridge (Building Complexes E, I-O-N, and L-M, Building F, the pottery kiln, as well as other areas excavated on the periphery). The present volume brings the evidence from all houses together and provides a reconstruction of life and society at Vronda in the LM IIIC period.